Analisis tingkat intensitas cahaya, kelembaban, suhu, dan kebisingan di Perpustakaan UIN Maulana Malik Ibrahim Malang - Ramadhani, Adelia Indah (Maliki Interdisciplinary Journal, 2025)
The UIN Maulana Malik Ibrahim Library is one of the facilities provided by the university to help support the student learning process. The aim of this research is to determine the level of light intensity, humidity, temperature and noise in the library of UIN Maulana Malik Ibrahim Malang. The research method used was testing using a 4 in 1 environment meter with repetition in 3 different places. The results obtained in this research were light intensity values ​​of 114.13 lux, humidity of 29.16 Rh, temperature of 28.5ºC, and noise of 49.3 dB. Based on these results, it can be concluded that the environmental conditions in the UIN Maulana Malik Ibrahim Malang library are still largely within the comfort standard category that can support student reading and learning activities, although there are several parameters that require further attention. The relatively low humidity value can potentially affect user comfort and the long-term durability of the book collection. Therefore, environmental control efforts are needed such as the addition of humidity control devices and better air circulation. Meanwhile, noise and temperature levels are still within the appropriate tolerance limits for the reading room. Overall, this study emphasizes the importance of regular monitoring of environmental factors in the library to ensure a conducive learning atmosphere and optimal utilization of available facilities by the entire academic community.